Students’ Perceptions toward Their Writing in EFL Setting: A Study at SMA YKBBB Leles Garut - Octaviana, Dwi Warry (Universitas PGRI Sumatera Barat, 2016)
The study concerned with writing subject. Writing subject, at any level of education, is considered as more complicated than the other language skills- listening, speaking, and reading. Due to this problem, the purposes of the study investigated the students’ perceptions toward their writing ability in classroom setting and determined the students’ difficulties factors in learning writing. The study employed qualitative research design and gathered data by ways of classroom observations and questionnaire. The results of the study were that the respondents had good perceptions. They gave positive and negative statements toward the English writing subject. Their negative perceptions were related to the difficulties of English writing process. Meanwhile, the positive perceptions they were related to the enrichment of the knowledge when they strove to write English. The study also found that most respondents stated that they had difficulties in writing English. These difficulties were mainly caused by their limitation of English grammar and less of English vocabulary. Besides that, the less of practice to write became a prime reason why they got low achievement of English writing.